2005
DOI: 10.1111/j.1745-4581.2005.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

A BIOSENSOR METHOD FOR A COMPETITIVE IMMUNOASSAY DETECTION OF STAPHYLOCOCCAL ENTEROTOXIN B (SEB) IN MILK2

Abstract: A sensitive and more rapid biosensor method for the detection of staphylococcal enterotoxins (SE) is needed by the food industry. Staphylococcal enterotoxin B (SEB) is highly heat resistant and is a potential bioterrorism agent. Our research objective was to develop a competitive immunoassay using a surface plasmon resonance (SPR) biosensor for the detection of SEB below 1 ng/mL [part per billion (ppb)] in fresh fluid milk. The assay consisted of SEB immobilization on the sensor surface. An anti‐SEB was allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…The displacements shown in Table 1 are lower than those reported for the analysis of SEB in milk (Medina 2005), where the spiked SEB was detected from 0.312–25 ppb. Presumably, there are two reasons for these differences.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…The displacements shown in Table 1 are lower than those reported for the analysis of SEB in milk (Medina 2005), where the spiked SEB was detected from 0.312–25 ppb. Presumably, there are two reasons for these differences.…”
Section: Resultscontrasting
confidence: 60%
“…The centrifuged samples were analyzed with the Biacore system without decanting the supernatant from the pellet. We have reported that in the analysis of SEB in ham extracts (Medina 2003) and in milk samples (Medina 2005), SEB and anti‐SEB IgG remained in the supernatant after centrifugation at 2961 × g. Figure 3 shows the dose response curves in five trials when 0, 1–40 ppb SEB spiked in whole egg supernatant and in homogenized egg was plotted against RU of excess and unbound anti‐SEA. In trials I–III, 10 µg anti‐SEA was added to a 1‐g sample.…”
Section: Resultsmentioning
confidence: 99%
“…Antibodies bound to toxin molecules from the sample are washed away and the mass increase on the surface measured. A LOD of 312 pg/ mL of SEB in fresh whole milk and skimmed milk could be achieved [110]. SEA was verifiable in a similar approach in spiked raw egg supernatants with an LOD of 1 ng/mL and a dynamic range of 1-40 ng/mL within 15-min of assay time [111].…”
Section: Botulinum Toxinsmentioning
confidence: 95%
“…Another sandwich immunoassay using SPR was also used for the determination of 2.5 ppb SEB-spiked ham tissue [ 90 ]. Moreover, a competitive pattern of SPR biosensor for detecting SEA and SEB in whole egg was established with the concentration range of 1–40 ng/mL SEA [ 91 ] and the LOD of SEB was lower than 1 ng/mL in fresh fluid milk [ 92 ]. SPR immunoassay combined mass spectrometry was established to detect SEB in spiked milk and mushrooms, and achieved a detection limit of 1 ng/mL [ 93 , 94 ].…”
Section: Se Identification Using Immunoassaysmentioning
confidence: 99%